Cognitive psychology : revisiting the classic studies - Eysenck, Michael W.; Groome, David, 1946- (Los Angeles ; London ; New Delhi ; Singapore ; Washington DC ; Boston : SAGE, 2015)
Revisiting the Classic Studies is a series of texts that introduces readers to the studies in psychology that changed the way we think about core topics in the discipline today. It provokes students to ask more interesting and challenging questions about the field by encouraging a deeper level of engagement both with the details of the studies themselves and with the nature of their contribution. Edited by leading scholars in their field and written by researchers at the cutting edge of these developments, the chapters in each text provide details of the original works and their theoretical and empirical impact, and then discuss the ways in which thinking and research has advanced in the years since the studies were conducted. Cognitive Psychology: Revisiting the Classic Studies traces 14 ground-breaking studies by researchers such as Chomsky, Tulving and Stroop to re-examine and reflect on their findings and engage in a lively discussion of the subsequent work that they have inspired. Suitable for students on cognitive psychology courses at all levels, as well as anyone with an enquiring mind.
An introduction to classic studies in cognitive psychology / Michael W. Eysenck and David Groome -- Attention : beyond Cherry's (1953) cocktail party problem / Michael W. Eysenck -- Perception : beyond Gibson's (1950) direct perception / Vicki Bruce and Yoav Tadmor -- Computational approaches to perception : beyond Marr's (1982) computational approach to vision / George Mather -- Perception and action : beyond Goodale and Milner's (1992) separate visual pathways / Glyn Humphreys -- Attention : beyond Stroop's (1935) colour-word interference phenomenon / Colin MacLeod -- Amnesia : beyond Scoville and Milner's (1957) research on HM / Howard Eichenbaum -- Working memory : beyond Baddeley and Hitch's (1974) working memory / Robert Logie -- Memory systems : beyond Tulving's (1972) episodic and semantic memory / Michael W. Eysenck and David Groome -- Encoding and retrieval : beyond Tulving and Thomson's (1973) encoding specificity principle / James Nairne -- Human problem solving : beyond Newell, Shaw, and Simon's (1958) theory of human problem solving / Fernand Gobet and Peter Lane -- Heuristics and biases : beyond Tversky and Kahneman's (1974) judgment under uncertainty / Klaus Fiedler and Momme von Sydow -- Decision making under risk : beyond Kahneman and Tversky's (1979) prospect theory / Ben Newell -- Language : beyond Chomsky's (1957) syntactic structures / Trevor Harley and Siobhan MacAndrew -- Cognitive neuropsychology of language : beyond Marshall and Newcombe's (1973) patterns of paralexia / Max Coltheart.
Includes bibliographical references and index.
Keywords: Cognitive psychology